Pengaruh Waktu Pengadukan Terhadap Sintesis Senyawa Kalkon Melalui Reaksi Kondensasi Claisen-Schmidt - Nur, Atiqah; Qodri, Udrika Lailatul; Atiqah , Sri Nur (Faculty of Pharmacy, University of Jember, 2024)
Chalcone compound is a secondary metabolite compound of the flavonoid class which has biological activity as an antibacterial. The purpose of this study was to determine the optimum stirring time in the synthesis of chalcone compounds using NaOH as an alkaline catalyst through the Claisen-Schmidt condensation reaction between acetophenone and benzaldehyde. The method for synthesizing chalcone compounds with stirring variations of 3 hours, 5 hours and 7 hours was carried out through three stages. The first stage is the manufacture of NaOH base catalyst. The second step is to mix acetophenone with NaOH solution to produce a nucleophilic enolate ion. The third step is to mix the enolate ion with benzaldehyde. The synthesized chalcone compound was characterized through organoleptic test, melting point test, solubility test, TLC test, UV-Vis Spectrophotometry, and FTIR. The characterization results show that each chalcone compound synthesized with variations in stirring time is generally produced in the form of crystals with color values of 13, 10 and 8 as seen in standard colors, melting point 50-51oC, highly soluble in chloroform and dichloromethane, slightly soluble in ethanol and practically insoluble in distilled water. The results of the TLC showed that the Rf value of the synthesized chalcone compound was different from the Rf value of the starting material. The results of UV-Vis spectrophotometry showed that there was a maximum absorption of benzoyl compounds in the 220 nm area and showed that there was a maximum absorption of cinnamyl compounds in the area of 370-390 nm. The FTIR spectrum shows the presence of functional groups =C-H (Alkene), C-H (Aromatic), C=C (Aromatic), C=C (Alkene), and C-H (Aromatic). The synthesis results show that the most optimal stirring time is 7 hours with a percent yield of 95.112%. The results of data analysis using the one way annova test showed that H0 was rejected and H1 was accepted, meaning that there was an effect of stirring time on the percent yield of the synthesized chalcone compound.